Successful management for vulvar epithelioid sarcoma during pregnancy: a rare case report - Guo, Xiaoqiao; Li, Runjun; Liu, Yan; Xiong, Ribo (Frontiers in Oncology, 2025)
Vulvar epithelioid sarcoma (ES) in pregnancy is an exceedingly rare condition, and only three reports are available to date. Optimal management is not well established. Herein, we report a 35-year-old woman who presented with a tender mass on the left labia majora at 33 weeks and 4 days of gestation. The patient underwent radical local resection of the lesion in the left vulva and left inguinal lymphadenectomy at 36 weeks and 4 days of gestation. Simultaneously, preterm cesarean section was performed because of mature fetus indicated by ultrasonography. Pathology of the lesion demonstrated a 7×5×5 cm-sized ES with the infiltration of surrounding adipose tissue, and no necrosis, hemorrhage, or venous invasion were identified. Six weeks after surgery, the patient underwent tumor resection due to recurrence. Then, adjuvant radiotherapy was performed with a dose of 40 Gy/10 cycles, followed by 15 Gy/3 cycles with a 10×10 cm field. The patient survived with neither recurrence nor complications at a 12-month follow-up. This case highlights management of a rare disease in pregnancy, with radical local resection of the lesion and lymphadenectomy combined with cesarean section.